A 25 mA cm−2 dye-sensitized solar cell based on a near-infrared-absorbing organic dye and application of the device in SSM-DSCs. Issue 11 (15th January 2020) - Cheema, Hammad; Watson, Jonathon; Peddapuram, Adithya; Delcamp, Jared H.
Abstract : A blue organic near infrared (NIR) absorbing sensitizer, AP25, is investigated for use in broadly absorbing dye-sensitized solar cells (DSCs). Abstract : A blue organic near infrared (NIR) absorbing sensitizer, AP25, is investigated for use in broadly absorbing dye-sensitized solar cells (DSCs). AP25 shows solar-to-electric conversion with an onset near 900 nm in DSC devices and a photocurrent near 25 mA cm −2 when co-sensitized. An all-organic SSM-DSC device reaches 10.3% PCE.